Overview of cellulose-based flexible materials for supercapacitors. Issue 12 (1st March 2021) - Sun, Zhe; Qu, Keqi; You, Yue; Huang, Zhanhua; Liu, Shouxin; Li, Jian; Hu, Qian; Guo, Zhanhu
Abstract : Cellulose-based materials as supercapacitor components including flexible electrodes, electrolytes and membranes are reviewed. Abstract : To tackle the crisis of fossil energy shortage and global warming, exploring a series of efficient, portable devices for the conversion/storage of clean and renewable energy sources has remained a significant topic. Supercapacitors as an advanced energy storage device have the properties of portability and stable performance, electrode materials especially flexible electrode materials as important components of supercapacitors have drawn great attention in various emerging fields such as portable, wearable electronics and memory materials. Based on high aspect ratios, specific surface areas, porosity, mechanical properties and excellent flexibility, natural polysaccharide cellulose and its derivatives have become promising building polymers for flexible electrode materials. In view of poor electrical conductivity and low areal capacitance, the compound modification of cellulose flexible materials and the corresponding application in flexible electrodes are reviewed. To further illustrate their versatile properties and performances, cellulose-based flexible electrolytes and membranes are summarized with detailed examples. Overall, this review covers recent advances regarding cellulose-based flexible materials for different components including electrodes, electrolytes and membranes used in supercapacitors and expects to provide references for further research of this promising material.